On the Concept of Procedural Responsibility: General Theoretical Analysis - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2023)
This article examines the concept of procedural responsibility. The position is defended according to which procedural responsibility is interpreted not as a type of legal responsibility, but as a complex legal institution consisting of the norms of both substantive and procedural law. In turn, procedural responsibility is divided into a number of sub-institutions, including criminal procedural responsibility, which is analyzed in more or less detail.